Problematic Internet use among resident physicians at St. Paul’s Hospital Millennium Medical College in Addis Ababa, Ethiopia - Yiknashewa Solomon Mekonnen; Selamawit Alemayehu Tessema; Solomon Dhabi Bedane; Askalemariam Bikiss Ali (BMC Psychiatry)
Abstract Background Problematic Internet use (PIU) is a growing concern in modern society. There is a limitation of epidemiologic data related to PIU. This is due to a lack of consensus on the definition and variability of assessment tools of PIU. PIU has been linked to a range of negative outcomes including depression, anxiety, social isolation, and poor academic or work performance. Resident physicians are at risk of exhibiting problematic internet use due to the high stress of academic demands, social isolation, long working hours, busy schedules, and internet access. There is limited research on this topic and targeting resident physicians in Ethiopia. This study aimed to determine the PIU prevalence and associated factors among resident physicians in SPHMMC, Ethiopia. Methods An institutional-based cross-sectional study was conducted from September 1, 2023, to November 25, 2023, at St. Paul’s Hospital Millennium Medical College (SPHMMC). This study included 417 physician residents who were selected using multistage sampling techniques, and Young’s Internet addiction test was used to assess PIU. To look for associations, logistic regression analysis, both binary and multivariable, was performed, and a p-value of < 0.05 was used to determine statistical significance. Results 414 participants were included in this study, with a response rate of 99.3%. The prevalence of PIU was 46.6%, with a 95% CI of 41.7–51.6%. The multivariable logistic regression model revealed that using the Internet for five or more hours per day (AOR: 1.84, 95% CI = 1.14, 2.99), having less than 7 h of actual sleep per night (AOR: 2.16, 95% CI = 1.03, 4.53), and having depression (AOR: 7.98, 95% CI = 2.47, 25.78) were significantly positively associated with PIU. In addition, factors such as being married (AOR: 0.42, 95% CI = 0.19, 0.91) and residents of the obstetrics and gynecology department (AOR: 0.32, 95% CI = 0.13, 0.81) were negatively associated with PIU. Conclusion This study revealed high PIU use among resident physicians at SPHMMC. Factors such as using the Internet for five or more hours per day, having less than seven hours of actual sleep per night, and having depression were found to be risk factors for PIU. On the other hand, being married and residents of the obstetrics and gynecology department were protective factors. Thus, creating awareness among medical residents about healthy tech habits and involving policymakers to develop guidelines for healthy internet use and awareness campaigns to reduce the impact of PIU is recommended.